Register of Builders Community in Javanese Speaking Communities - Sudaryanto, Memet; Sari, Eka Dyah Puspita; Rohmadi, Muhammad (Universitas Negeri Semarang, 2021)
The registers of builders in the Javanese speaking community show unique data. It is important to describe the purpose, the characteristics of the formation, and the social context that influence speech to show the complexity of registers that appear in the language community of builders. In order to achieve these objectives, a descriptive qualitative analysis was performed on conversations among builders using a phenomenological approach in a sociolinguistic perspective. Data were taken from conversations between builders, builders with the foreman, and clients with builders. Data were obtained from social media conversations in private groups through passive observer. The data were validated through triangulation method. Based on the results of the interactive analysis, it was found that (1) the purpose of using registers was to make the conversation effective so they were easily accepted and to show the identity of community members, (2) registers of construction community members in Javanese-speaking societies used nominal markers, numerals, adjectives, and verbs, (3) the socio-cultural context built in the conversation between builders was shown from the speaker's needs and speech responses. The speech produced by members of the building community speaking in Javanese society included idealism, norms, rules, and behavior as habits in the community. Sociolinguistics, as a branch of linguistics that studies the interplay between language behavior and social behavior, showed that the builder community used language in socializing to convey and express their field of work and to get acquinted with new members of the community with a special language. Based on the results of data triangulation, it showed that the tendency of Javanese speakers in the construction community did not understand interpersonal relationships and privacy in conversation.